Representasi Budaya Indonesia Dalam Logo G20 Indonesia 2023 - Ahmad Fatoni; Jupriani Jupriani (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
In this research, the author identified the visual forms found in the G20 Indonesia 2022 logo. These forms were identified in order to determine the representation of Indonesian culture contained in the G20 Indonesia 2022 logo. The author used descriptive research with a qualitative approach. The visual form and meaning of the G20 Indonesia 2022 logo were analyzed through preiconographical, iconographic and iconological theories which were explained by Edward Panofsky. Visual elements such as shape, color, typography, contained in the G20 Indonesia 2022 logo were identified through this process. These three steps examine the hidden meaning of the G20 Indonesia 2022 logo which is linked to basic cultural mentality. These steps became the basis for researchers to analyze the data. Researchers analyzed the visual form and meaning of the G20 Indonesia 2022 logo to determine the relationship between the logo and Indonesian culture. Analysis of the visual appearance and meaning was carried out to conclude the representation of Indonesian culture in the G20 Indonesia 2022 logo. Based on the findings of this research, it was concluded that the G20 Indonesia 2022 logo has a form and meaning that represents Indonesian culture.